Factores del estrés e incidencia en el desempeño laboral de los servidores públicos de la EMAPASOSQ-EP. Período 2021 - Santos Rueda, Luis Andrés (2022)
The present study was developed under the objective of analyzing the stress factors in the public servants of the Municipal Public Company of Potable Water, and Sewage, Environmental Sanitation, Works and Services in Quininde canton, EMAPASOSQ-EP for the improvement of work performance. Information collection methodologies were used through evaluative instruments such as the survey and interview to which a Cronbach's Alpha test reliability analysis was applied, together with the Pearson correlational method to show the relationship between the study variables. The results show shortcomings in aspects of integration, motivation and work environment, lack of institutional commitment, work demands, lack of training, limitations for the development of assigned tasks and inadequate levels of satisfaction of the external user, in the context of the association of the variables studied, there is no significant linear correlation between them, since the results of the p value (0.973) are above the stipulated significance (p=0.05). The deficiencies detected could lead to inadequate levels of productivity in public servants, affecting the delivery of the service to users by the institution, for which it is unavoidable to apply the corrective actions proposed in the improvement plan for their respective improvements.